Gamified Vocabulary Learning for Young English Learners Through Snowball Throwing - Kahar, Siti Rahmawati; Aritonang, Parjolo; Ulorlo, Yulia Josina; Apalem, Corneles Rubenaser; Hasyim, Gama Rani (Civiliza Publishing, 2025)
This community service program investigated the application snowball throwing as an instrument to augment English vocabulary acquisition among fifth-grade learners at SD Kristen 1 Dobo, situated in the Aru Islands. Teaching of English has some challenges, especially in primary school. The students do not speak English as their mother language; therefore, it is quite difficult for them to acquire English fluently particularly in rural areas. The program encompassed 29 participants and extended over three sessions, during which students engaged in cooperative gameplay that integrated written vocabulary, physical activity, and verbal expression. This approach facilitated students' comprehension and retention of vocabulary, provided them with lists of words, and instructed them on the accurate pronunciation of these terms through the use of engaging visuals and thematic content, while also modifying the classroom environment to enhance the learning process. The findings revealed a notable enhancement in vocabulary acquisition, heightened student motivation, and favorable teacher feedback. These results underscore the efficacy of embodied, game-based learning in fostering language development within an Indonesian primary educational context.